Investigation of Dipicolinic Acid Isosteres for the Inhibition of Metallo‐β‐Lactamases. (24th May 2019) - Chen, Allie Y.; Thomas, Pei W.; Cheng, Zishuo; Xu, Nasa Y.; Tierney, David L.; Crowder, Michael W.; Fast, Walter; Cohen, Seth M.
Abstract: New Delhi metallo‐β‐lactamase‐1 (NDM‐1) poses an immediate threat to our most effective and widely prescribed drugs, the β‐lactam‐containing class of antibiotics. There are no clinically relevant inhibitors to combat NDM‐1, despite significant efforts toward their development. Inhibitors that use a carboxylic acid motif for binding the Zn II ions in the active site of NDM‐1 make up a large portion of the >500 inhibitors reported to date. New and structurally diverse scaffolds for inhibitor development are needed urgently. Herein we report the isosteric replacement of one carboxylate group of dipicolinic acid (DPA) to obtain DPA isosteres with good inhibitory activity against NDM‐1 (and related metallo‐β‐lactamases, IMP‐1 and VIM‐2). It was determined that the choice of carboxylate isostere influences both the potency of NDM‐1 inhibition and the mechanism of action. Additionally, we show that an isostere with a metal‐stripping mechanism can be re‐engineered into an inhibitor that favors ternary complex formation. This work provides a roadmap for future isosteric replacement of routinely used metal binding motifs (i.e., carboxylic acids) for the generation of new entities in NDM‐1 inhibitor design and development. Abstract : Re‐engineering isosteres : Dipicolinic acid isosteres were evaluated against metallo‐β‐lactamases. The concept of isosteres is used to show that the choice of carboxylate isostere impacts not only inhibition potency, but also the mechanism of action. This study demonstrates the utility of isosteric replacement for routinely used metal binding motifs (e.g., carboxylic acids) in metalloenzyme inhibitor development.